Abnormal flow pattern of low wall shear stress and high oscillatory shear index in spontaneous vertebral artery dissection with vertebral artery hypoplasia - Bao, Jiajia; Gan, Xinling; Feng, Wentao; Li, Yanbo; Qiu, Yue; Zhou, Muke; Guo, Jian; He, Li (Frontiers in Neuroscience, 2023)
Introduction Spontaneous vertebral artery dissection (sVAD) might tend to develop in vertebral artery hypoplasia (VAH) with hemodynamic dysfunction and it is crucial to assess hemodynamics in sVAD with VAH to investigate this hypothesis. This retrospective study aimed to quantify hemodynamic parameters in patients with sVAD with VAH. Methods Patients who had suffered ischemic stroke due to an sVAD of VAH were enrolled in this retrospective study. The geometries of 14 patients (28 vessels) were reconstructed using Mimics and Geomagic Studio software from CT angiography (CTA). ANSYS ICEM and ANSYS FLUENT were utilized for mesh generation, set boundary conditions, solve governing equations, and perform numerical simulations. Slices were obtained at the upstream area, dissection or midstream area and downstream area of each VA. The blood flow patterns were visualized through instantaneous streamline and pressure at peak systole and late diastole. The hemodynamic parameters included pressure, velocity, time-averaged blood flow, time-averaged wall shear stress (TAWSS), oscillatory shear index (OSI), endothelial cell action potential (ECAP), relative residence time (RRT) and time-averaged nitric oxide production rate (TARNO). Results Significant focal increased velocity was present in the dissection area of steno-occlusive sVAD with VAH compared to other nondissected areas (0.910 m/s vs. 0.449 vs. 0.566, p < 0.001), while focal slow flow velocity was observed in the dissection area of aneurysmal dilatative sVAD with VAH according to velocity streamlines. Steno-occlusive sVAD with VAH arteries had a lower time-averaged blood flow (0.499 cm3/s vs. 2.268, p < 0.001), lower TAWSS (1.115 Pa vs. 2.437, p = 0.001), higher OSI (0.248 vs. 0.173, p = 0.006), higher ECAP (0.328 Pa−1 vs. 0.094, p = 0.002), higher RRT (3.519 Pa−1 vs. 1.044, p = 0.001) and deceased TARNO (104.014 nM/s vs. 158.195, p < 0.001) than the contralateral VAs. Conclusion Steno-occlusive sVAD with VAH patients had abnormal blood flow patterns of focal increased velocity, low time-averaged blood flow, low TAWSS, high OSI, high ECAP, high RRT and decreased TARNO. These results provide a good basis for further investigation of sVAD hemodynamics and support the applicability of the CFD method in testing the hemodynamic hypothesis of sVAD. More detailed hemodynamic conditions with different stages of sVAD are warranted in the future.